Analyzing cosmic-ray muons in the experimental paths of the "Mathematical High School" Project. Issue 1 (1st February 2023) - Aramo, C.; Colalillo, R.; Tortoriello, F.S.; Veronesi, I.
Abstract: The Mathematical High School (MHS) Project is a research project involving 160 high schools and 26 Italian universities in which experimental research paths are deepened to explore mathematics as a universal language and as a link between the various areas of both humanistic and scientific knowledge. These activities are developed with the collaboration of internationally recognized research institutions. In particular, in the MHS schools, the research group of the Mathematics Department of the University of Salerno in collaboration with INFN (National Institute of Nuclear Physics) Naples division, offers laboratory activities of data analysis on cosmic rays. Students, guided by the researchers, use the CRC (Cosmic Rays Cube), a portable muon detector, to carry out an experimental activity, from the data taking to the analysis. They study what cosmic rays are, where they come from and, in particular, the characteristics of comic-ray muons produced in the Earth atmosphere. Mathematics becomes the instrument to interpret data collected by the detector, measure the muon flux and reconstruct their direction. Using dedicated software, students experience the activity of the researchers. Working in team, they deal with high-profile scientific issues usually not developed in the curricular educational paths.